Seeing is believing (opinion letter) - Shields, Linda (Elsevier Science, 2011)
We should not be surprised by the strength of the anti-immunisation lobby (15 January, p 46). In rich nations, the majority of the population has never seen the diseases that we recommend parents vaccinate their children against. Immunisation has been so effective that diseases such as diphtheria and polio have all but disappeared. To overcome the misinformation and resistance, we should use outlets such as YouTube and Facebook to show photos and films of children suffering from all the diseases which we immunise against. The anti-immunisation lobby uses shock tactics and social media to fight their cause. So should we.